2014
DOI: 10.3390/ijms15058360
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiprotozoal Activity of Abietane Diterpenoids Isolated from Plectranthus barbatus Andr.

Abstract: Chromatographic separation of the n-hexane extract of the aerial part of Plectranthus barbatus led to the isolation of five abietane-type diterpenes: dehydroabietane (1); 5,6-didehydro-7-hydroxy-taxodone (2); taxodione (3); 20-deoxocarnosol (4) and 6α,11,12,-trihydroxy-7β,20-epoxy-8,11,13-abietatriene (5). The structures were determined using spectroscopic methods including one- and two-dimensional NMR methods. Compounds (1)–(3) and (5) are isolated here for the first time from the genus Plectranthus. The isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…A clerodane diterpene in L. donovani exhibited caspase-3/-7-like protease activity and genomic DNA fragmentation, induced mitochondrial dysfunction, and caused an oxidative stressmediated apoptotic cell death (Kathuria et al, 2014), while kaurenoic acid triggered the NLRP12/IL-1β/ cNOS/NO mechanism in Leishmania amazonensis (Miranda et al, 2015). A number of promising leishmicidal diterpenes have been reported (Sinha et al, 2000;Sairafianpour et al, 2001;Lala et al, 2003;Habtemariam, 2003;González et al, 2005;Fokialakis et al, 2006;Brito et al, 2006;Suryawanshi et al, 2008;Roy et al, 2010;Dos Santos et al, 2011;Mondal et al, 2013;Soares et al, 2013;Santos et al, 2013;Mothana et al, 2014;Moreira et al, 2014;Mokoka et al, 2014;Falodun et al, 2014;Demarchi et al, 2015;da Silva et al, 2015;Mizuno et al, 2015;Lima et al, 2015; Leprosy. It is also known as Hansen's disease, a longterm infection caused by the bacteria Mycobacterium leprae and Mycobacterium lepromatosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clerodane diterpene in L. donovani exhibited caspase-3/-7-like protease activity and genomic DNA fragmentation, induced mitochondrial dysfunction, and caused an oxidative stressmediated apoptotic cell death (Kathuria et al, 2014), while kaurenoic acid triggered the NLRP12/IL-1β/ cNOS/NO mechanism in Leishmania amazonensis (Miranda et al, 2015). A number of promising leishmicidal diterpenes have been reported (Sinha et al, 2000;Sairafianpour et al, 2001;Lala et al, 2003;Habtemariam, 2003;González et al, 2005;Fokialakis et al, 2006;Brito et al, 2006;Suryawanshi et al, 2008;Roy et al, 2010;Dos Santos et al, 2011;Mondal et al, 2013;Soares et al, 2013;Santos et al, 2013;Mothana et al, 2014;Moreira et al, 2014;Mokoka et al, 2014;Falodun et al, 2014;Demarchi et al, 2015;da Silva et al, 2015;Mizuno et al, 2015;Lima et al, 2015; Leprosy. It is also known as Hansen's disease, a longterm infection caused by the bacteria Mycobacterium leprae and Mycobacterium lepromatosis.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, diterpenes in nanoformulations (Roy et al, 2010;Mondal et al, 2013) as well as their laboratory derivatives have been reported to exhibit promising anti-NTDs activities (Watson and Preedy, 2010;Mander and Liu, 2010). Additionally, a number of diterpenes have been reported to act against multiple strains responsible for a particular NTD (Sanchez et al, 2006;Dea-Ayuela et al, 2016;Johnson et al, 1993;Riel et al, 2002;Clarkson et al, 2003;Kalauni et al, 2006;Ojo-Amaize et al, 2007;Wangchuk et al, 2010;González et al, 2014;Namukobe et al, 2015;Liu et al, 1997;Prabu et al, 2015;Encarnación-Dimayuga et al, 2006;Rijo et al, 2010;Arai et al, 2014;Xu et al, 2014a;Xu et al, 2014b) and NTDs (Schmidt et al, 2011;Al Musayeib et al, 2014;Ramírez-Macías et al, 2012;Mothana et al, 2014;Falodun et al, 2014;Mizuno et al, 2015;Mongkolvisut and Sutthivaiyakit, 2007;Rangkaew et al, 2009;Ospina and Rodríguez, 2009;Lekphrom et al, 2010;Almutairi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other 10 known compounds were identified as 2 α , 3 α , 24-trihydroxyurs-12, 20(30)-dien-28oic acid ( 2 ) [8] , 6, 7-dehydroroyleanone ( 3 ) [9] , horminone ( 4 ) [10] , 7- O -methylhorminone ( 5 ) [10] , sugiol ( 6 ) [11] , demethylcryptojaponol ( 7 ) [12] , 14-deoxycoleon U ( 8 ) [13] , 5, 6-didehydro-7-hydroxy-taxodone ( 9 ) [14] , ferruginol ( 10 ) [15] , and dichroanone ( 11 ) [16] , by comparing their NMR data with those reported in the literature. Inside, compounds 1 , 2 and 5 were isolated from the genus Salvia for the first time, and 1 , 2 , 5–11 were firstly isolated from S. deserta .…”
Section: Resultsmentioning
confidence: 99%
“…Abietane diterpenes isolated from aerial parts of Plectranthus barbatus showed remarkable activity with acceptable selectivity against the blood parasites Plasmodium falciparum (malaria) and Trypanosoma brucei (sleeping sickness in animals). Nonspecific antiprotozoal activity was also detected and is likely due to the compound's high cytotoxicity (Mothana et al 2014). This plant also demonstrates significant anticancer activity (Duke and Ayensu 1985).…”
Section: Medicinal Foods In the Dietmentioning
confidence: 99%